1998
DOI: 10.1086/314430
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Famciclovir and Interferon‐α for the Treatment of Chronic Hepatitis B

Abstract: Interferon-alpha (IFN-alpha) treatment results in long-term remissions in only 25%-40% of patients with chronic hepatitis B virus (HBV) infection. Famciclovir, the oral prodrug of penciclovir, inhibits HBV DNA replication. Five adults with chronic HBV infection in whom previous IFN-alpha therapy had failed were treated in a pilot study of overlapping IFN-alpha and famciclovir therapy totaling 20 weeks. HBV DNA levels decreased by 0.9 log units during the initial 4-week period of famciclovir alone, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…Although 2 international, multicenter trials 13,27 have not shown significantly improved responses with a combination of lamivudine and interferon for 6 months, these do not necessarily predict results with other combinations. Several other regimens, [28][29][30][31] including 2 or more nucleoside analogues or a nucleoside analogue plus immunomodulatory therapy, are being considered. …”
mentioning
confidence: 99%
“…Although 2 international, multicenter trials 13,27 have not shown significantly improved responses with a combination of lamivudine and interferon for 6 months, these do not necessarily predict results with other combinations. Several other regimens, [28][29][30][31] including 2 or more nucleoside analogues or a nucleoside analogue plus immunomodulatory therapy, are being considered. …”
mentioning
confidence: 99%
“…Unfortunately, the viral load increased once again in four of the patients after stopping the medication and three of them remained HBeAg positive at all times during the study. 73 In vitro studies support the use of two or more nucleoside analogues for HBV infection. The combination of lamivudine with either interferon alpha or penciclovir significantly enhances the antiviral effectiveness of these agents against HBV replication in 2.2.15 cell culture, an HBV-producing human hepatoblastoma cell line, the result of which has been shown to predict antiviral responses in vivo.…”
Section: Hepatitis B Combination Therapymentioning
confidence: 99%
“…6 Preliminary clinical trials of newer nucleoside analogues in combination with IFN-␣ have been similarly disappointing, perhaps because a large proportion of patients in these trials had failed IFN-␣ therapy. 26,27 On the other hand, preclinical results suggest that the newer anti-HBV nucleoside analogues are at least additive in their effects and that antagonistic interactions are rare. [28][29][30] As the number of safe and effective anti-HBV drugs increases, the means to assess, quantify, and compare drug efficacy and drug interactions in a standardized manner will become an important issue in both preclinical tests and clinical trials.…”
Section: Combination Chemotherapy and Drug Resistancementioning
confidence: 99%
“…Whether the best approach will involve using additional nucleosides or adding immunomodulators to nucleoside combinations is not yet known. Preliminary reports from ongoing phase III clinical trials of IFN-␣ in combination with lamivudine 26 or famciclovir 27 have already appeared and suggest that either combination is effective with long-term administration. The next logical step may be to initiate trials of triple therapy with IFN-␣, lamivudine, and famciclovir.…”
Section: Future Prospectsmentioning
confidence: 99%